2018
DOI: 10.1186/s12905-017-0497-5
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and determinants of contraceptive usage among women of reproductive age from the Digo community residing in Kwale, Kenya: results from a cross-sectional household survey

Abstract: BackgroundContraceptive usage has been associated with improved maternal and child health (MCH) outcomes. Despite significant resources being allocated to programs, there has been sub-optimal uptake of contraception, especially in the developing world. It is important therefore, to granulate factors that determine uptake and utilization of contraceptive services so as to inform effective programming.MethodsBetween March and December 2015, we conducted a cross-sectional survey among women of reproductive age (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 15 publications
5
26
0
Order By: Relevance
“…When a woman got formal education, she would have more chances to use contraception. This means that education plays an important role in the usage of modern contraceptives (Mochache et al, 2018). The positive effect of formal education on the usage of contraceptives can be explained in two ways:…”
Section: Discussionmentioning
confidence: 99%
“…When a woman got formal education, she would have more chances to use contraception. This means that education plays an important role in the usage of modern contraceptives (Mochache et al, 2018). The positive effect of formal education on the usage of contraceptives can be explained in two ways:…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that reported a reduction of maternal mortality with the use of contraceptive. 8,18,19 Coping mechanisms should focus or be done based on the specific social determinant that leads to maternal death. Some of the major mechanisms that were used in coping to the social determinant to maternal health in Africa include social participation, empowering women through education for enhancing their autonomy in order to create freedom of making health-related decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Education regarding family planning service and supply points helped to decrease the level of unintended pregnancy. This is related to their role in providing information on family planning and increasing the utilization [ 32 , 33 ].…”
Section: Main Textmentioning
confidence: 99%